Repeated Exposure to Illusory Sense of Body Ownership and Agency Over a Moving Virtual Body Improves Executive Functioning and Increases Prefrontal Cortex Activity in the Elderly - Burin, Dalila; Kawashima, Ryuta (Frontiers in Human Neuroscience, 2021)
We previously showed that the illusory sense of ownership and agency over a moving body in immersive virtual reality (displayed in first person perspective) can trigger subjective and physiological reactions on the real subject’s body and, therefore, an acute improvement of cognitive functions after a single session of high-intensity intermittent exercise performed exclusively by the own virtual body, similarly to what happens when we actually do physical activity. As well as confirming previous results, here we aimed at finding in the elderly an increased improvement after a longer virtual training with similar characteristics. 42 healthy older subjects (28 females, average age 71.71 years) completed a parallel-group RCT (UMIN000039843, umin.ac.jp) including an adapted version of the virtual training previously used: while sitting, participants observed the virtual body in first person perspective (1PP) or third person perspective (3PP) performing 20 minutes of virtual high-intensity intermittent exercise (vHIE, the avatar switched between fast and slow walking every two minutes). This was repeated twice a week for six weeks. During the vHIE, we measured the heart rate and administered questionnaires to evaluate illusory body ownership and agency. Before the beginning of the intervention, immediately after the first session of vHIE, and at the end of the entire intervention, we evaluated the cognitive performance at the Stroop task with the online recording of hemodynamic activity over the left dorsolateral prefrontal cortex. While we confirm previous results regarding the virtual illusion and its physiological effects, we did not find significant cognitive or neural improvement immediately after the first vHIE session. As a novelty, in 1PP group only we detected a significant decrease in response time the Stroop task in the post intervention assessment, compared to its baseline; coherently, we found an increased activation on lDLPFC after the entire intervention. While the current results strengthen the impact of the virtual full-body illusion and its physiological consequences on elderly too, they might have stronger and more established body representations; perhaps, a longer and increased exposure to those illusions is necessary to initiate the cascade of events that culminates to the improved cognitive performance.